MENEROPONG SISTEM PRODUKSI DALAM EKONOMI KONVENSIONAL - Moh Subhan (Ulumuna: Jurnal Studi Keilsman, 2018)
The production is an activity related to the way how INPUT can be used to generate a product (OUTPUT). Production, distribution and consumption is a series of interrelated economic activities. All three are influence each other, but the production is the base of economic activity. The production is human activity to produce goods and services which are then exploited by consumers. Production activities in perspective of Economics of Islam is not only oriented to maximize profits (maximizing of profit) consequential matter, regardless of the existing rules, as conventional economic paradigms, but more of that production in Islam is more oriented on expression of obedience to God's commands, namely to provide for the needs of both spiritual as well as material in order to create maslahah maximizer in the form of benefits and blessings can sustain existence as well as the height degree of human beings. Production factors include; capital (Capital/Ra'sul maal), labor (Labor/' charity), natural resources (Resouches/ "Ardh.).